2007
DOI: 10.1128/aem.02970-06
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Selected Hydrogen Bonding and Ionic Interactions fromAspergillus fumigatusPhytase Structure Improves the Thermostability ofAspergillus nigerPhyA Phytase

Abstract: Although it has been widely used as a feed supplement to reduce manure phosphorus pollution of swine and poultry, Aspergillus niger PhyA phytase is unable to withstand heat inactivation during feed pelleting. Crystal structure comparisons with its close homolog, the thermostable Aspergillus fumigatus phytase (Afp), suggest associations of thermostability with several key residues (E35, S42, R168, and R248) that form a hydrogen bond network in the E35-to-S42 region and ionic interactions between R168 and D161 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…It is known that both hydrogen bonding and hydrophobic interactions play important roles in the thermal stability of proteins. Previously, a number of studies have shown that the introduction of these interactions into thermophilic proteins is an efficient approach for further enhancing their stability (37,38). In the present study, analysis of the structure models of the mutants also showed that new hydrogen bonds and/or hydrophobic interactions were introduced to the disorder loop of Phe490-Asp513 (Fig.…”
Section: Resultssupporting
confidence: 61%
“…It is known that both hydrogen bonding and hydrophobic interactions play important roles in the thermal stability of proteins. Previously, a number of studies have shown that the introduction of these interactions into thermophilic proteins is an efficient approach for further enhancing their stability (37,38). In the present study, analysis of the structure models of the mutants also showed that new hydrogen bonds and/or hydrophobic interactions were introduced to the disorder loop of Phe490-Asp513 (Fig.…”
Section: Resultssupporting
confidence: 61%
“…Thermostability is a particularly important issue since feed pelleting is commonly performed at temperatures between 65 °C and 95 °C. About 51% to 63% of the original activity of fusion phytase remained after incubation at 75 °C to 95 °C for 10 min without a protective agent, which was more thermostable than phyA m phytase (Fig.6c) and phyA mutant which retained 20% activity after being heated at 80 °C for 10 min (Zhang et al, 2007). The expressed phyA m , phyCs and fusion phyA m -phyCs phytases showed a broad and diffuse band in SDS-PAGE due to the heavy glycosylation (Fig.5) as described by Markus et al(1999) and Zou et al(2006).…”
Section: Discussionmentioning
confidence: 96%
“…All purification steps were carried out at 4 °C unless otherwise stated (Janne et al, 1998;Zou et al, 2006;Zhang et al, 2007). The culture supernatant obtained by centrifugation at 5000×g for 10 min was supplemented with CaCl 2 to a final concentration of 2 mmol/L.…”
Section: Purification Of Recombinant Fusion Phytasementioning
confidence: 99%
“…The A. fumigatus phytase (Afp) which shares high sequence identity to AnPhyA (sequence identity, 60.5 %) but exhibits exceptional heat resilience was chosen as a template for AnPhyA modification [26,49]. According to the sequence alignment of two Aspergillus phytases and analysis of the Afp 3D structure, four Afp-unique residues that involve in hydrogen bond and salt bridge formations were identified [50,51]. The AnPhyA mutant harboring the four residues in the corresponding positions displayed 20 % higher residual activity at 100°C [51].…”
Section: Homologous Alignmentmentioning
confidence: 99%
“…According to the sequence alignment of two Aspergillus phytases and analysis of the Afp 3D structure, four Afp-unique residues that involve in hydrogen bond and salt bridge formations were identified [50,51]. The AnPhyA mutant harboring the four residues in the corresponding positions displayed 20 % higher residual activity at 100°C [51]. Notably, the mutant residues A35E and P42S are located within the fungal HAP unique N-terminal region and may stabilize the local structure through forming a hydrogen bond to each other (Fig.…”
Section: Homologous Alignmentmentioning
confidence: 99%